PENGARUH MODEL PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP PEMAHAMAN SISWA PADA MATERI BILANGAN BULAT - AINUL MARHAMAH HASIBUAN (LP2MTBM MAKARIOZ, 2020)
This research aims to find out the understanding of students' mathematics before and after using the Realistic MathematicsLearning Model, whether there is an influence on the use of realistic mathematics learning on students' mathematicalunderstanding. This research is a quantitative research experiment. The population of this study is grade IV SD Negeri200211 Padangmatinggi and its sample with two classes namely grades IV-A and IV-B. Instruments used in data collectionare essay tests. The data analysis technique is to use the formula